Study on strength prediction of grouting filling body in karst areas considering pressure filter effect - Yan, Zhao; Jihong, Duan; Yinglin, Liu; Mengshan, Xie; Wen, Li (Frontiers in Earth Science, 2025)
The slurry within the grouting pressure and karst boundary constraints produces a pressure filtration effect, resulting in the initial consolidation strength of the embankment curtain stone body in karst areas being significantly higher than the natural consolidation strength of the slurry. Consequently, using the natural consolidation strength of the slurry as the initial condition for constructing the curtain life prediction model often leads to substantial deviations from engineering practice. To address this issue, this paper first derives a theoretical formula for calculating the initial consolidation strength of the grouted curtain body, taking into account the erosive effects of karst water ions and the pressure-filtering effect. Secondly, a life prediction model for grouting curtains in karst areas, which incorporates the pressure-filtering effect, is developed, and its feasibility is demonstrated through indoor accelerated testing. Finally, the research findings were successfully applied to guide the curtain de-reinforcement project at the Yingpan Reservoir in Yunnan Province. The results indicate that the theoretical formula for the initial consolidation strength of the grouted curtain body, which considers the pressure-filtering effect, more accurately characterizes the initial conditions of the curtain. Additionally, the theoretical values derived from the curtain life prediction model closely align with the accelerated experimental test values, with an error margin of less than 15%. This demonstrates that the theoretical prediction model can effectively forecast the service life of the curtain body under conditions of karst water erosion. The successful engineering application further confirms the feasibility and practicality of the theoretical prediction model. Given the increasing number of similar cases, the research findings hold significant application potential and practical value.